What the collapse of the ensemble Kalman filter tells us about particle filters. Issue 1 (1st January 2017) - Morzfeld, Matthias; Hodyss, Daniel; Snyder, Chris
Abstract : The ensemble Kalman filter (EnKF) is a reliable data assimilation tool for high-dimensional meteorological problems. On the other hand, the EnKF can be interpreted as a particle filter, and particle filters (PF) collapse in high-dimensional problems. We explain that these seemingly contradictory statements offer insights about how PF function in certain high-dimensional problems, and in particular support recent efforts in meteorology to 'localize' particle filters, i.e. to restrict the influence of an observation to its neighbourhood.